Intestinal Dysbiosis, Gut Hyperpermeability and Bacterial Translocation: Missing Links Between Depression, Obesity and Type 2 Diabetes - Slyepchenko, Anastasiya; Maes, Michael; Machado-Vieira, Rodrigo; Anderson, George; Solmi, Marco; Sanz, Yolanda; Berk, Michael; A. Kohler, Cristiano; F. Carvalho, Andre (Current Pharmaceutical Design, 2016)
The comorbid prevalence of major depressive disorder (MDD) with obesity and type II diabetes mellitus reflects the existence of a subset of individuals with a complex common pathophysiology and overlapping risk factors. Such comorbid disease presentations imply a number of difficulties, including: decreased treatment responsivity and adherence; altered glycemic control and increased risk of wider medical complications. A number of factors link MDD to metabolic-associated disorders, including: higher rates of shared risk factors such as poor diet and physical inactivity and biological elements including increased inflammation; insulin resistance; oxidative and nitrosative stress; and mitochondrial dysfunction. All of these biological factors have been extensively investigated in the pathophysiology of obesity and type 2 diabetes mellitus as well as MDD. In this review, we aim to: (1) overview the epidemiological links between MDD, obesity and type 2 diabetes mellitus; (2) discuss the role of synergistic neurotoxic effects in MDD comorbid with obesity, and type 2 diabetes mellitus; (3) review evidence of intestinal dysbiosis, leaky gut and increased bacterial translocation, in the pathophysiology of MDD, obesity and type 2 diabetes mellitus; and (4) propose a model in which the gut-brain axis could play a pivotal role in the comorbidity of these disorders.
Keywords: obesity